A Stochastic Model for the Expected Time to Recruitment in a Single Graded Manpower System with Two Thresholds Using Bivariate Policy - and A. Srinivasan, J.B. Esther Clara* (Recent Research in Science and Technology, 2010)
In this paper, an organization subjected to random exit of personnel due to policy decisions taken by the organization is considered. There is an associated loss of manpower if a person quits. As the exit of personnel is unpredictable, a new recruitment policy involving two thresholds - one is optional and the other one mandatory is suggested to enable the organization to plan its decision on recruitment. Based on shock model approach, a mathematical model is constructed using an appropriate bivariate policy of recruitment. The analytical expression for the mean and variance of the time to recruitment are obtained when i) the loss of manhours process forms a sequence of independent and identically distributed continuous random variables ii) the inter-decision times are independent and identically distributed continuous random variables and iii) the optional threshold level as well as the mandatory threshold level are also continuous random variables. The results are numerically illustrated and analyzed by assuming specific distributions.